Tissue Factor Is Rapidly Elevated in Plasma Collected from the Pericardial Cavity during Cardiopulmonary Bypass - Philippou, Helen; Adami, Antonella; Davidson, Simon J.; Pepper, John R.; Burman, John F.; Lane, David A. (Thrombosis and Haemostasis, 2000)
There is growing evidence that the tissue factor/factor VIIa pathway of coagulation is enhanced during cardiopulmonary bypass. Hitherto, available evidence has suggested that upregulated monocyte bound tissue factor is made available, either in the blood collected from the site of surgery or on circulating cells. However, cellular upregulation is slow, while generation of factor VIIa in blood collected from the pericardial cavity is rapid. We have therefore investigated the possibility of an alternative source of tissue factor, plasma (as opposed to cellular) tissue factor in blood samples taken from the central vein catheter (systemic circulation) and collected from the pericardial cavity during cardiopulmonary bypass. Six patients undergoing first time cardiopulmonary bypass grafting were studied. Tissue factor antigen was found to be rapidly elevated (by 15 min) in the pericardial plasma, ∼5-fold above systemic levels (p <0.004). Similar elevations were found in markers of coagulation activation, factor VIIa antigen (p = 0.066), prothrombin fragment F1+2 (p <0.003) and thrombin-antithrombin complex (p <0.03). To explore whether plasma tissue factor was (or had been) functionally active, factor VIIa was measured also with the soluble tissue factor functional assay after removal of heparin. Functional factor VIIa activity fell significantly in the systemic circulation, probably due to the heparin-induced increase (∼15-fold) in tissue factor pathway inhibitor (TFPI), but was elevated in pericardial blood compared with that taken from the central line catheter (p <0.006). These results demonstrate that both components of the activation complex for the extrinsic pathway of coagulation are rapidly generated in pericardial blood during bypass.
Keywords: Tissue factor; factor VIIa; cardiopulmonary bypass; tissue factor pathway inhibitor; heparin